2012
DOI: 10.1002/micr.20952
|View full text |Cite
|
Sign up to set email alerts
|

The free anterolateral thigh musculocutaneous flap for head and neck reconstruction: One surgeon's experience in 92 cases

Abstract: The free ALT musculocutaneous flap offers unique advantages in head and neck reconstructions including adequate bulk when needed, obliteration of dead space, support for the soft tissues of the face, low donor-site morbidity, and harvesting without needing for perforators dissection, allowing for optimal patient outcome. Excessive bulky and thickness of subcutaneous tissue, especially in occidental population, have to be considered as the main disadvantages of this technique, finally the high incidence of hair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
56
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 31 publications
(27 reference statements)
1
56
0
Order By: Relevance
“…The anterolateral thigh flap (ALT) is another workhorse flap for soft‐tissue reconstructions in the lower extremities. The ALT flap can provide a large skin paddle nourished by a long and large‐caliber pedicle . However, all free flaps have the common drawback of the difficulty of choosing the recipient vessels because of the poor local wound condition in the lower extremity .…”
Section: Discussionmentioning
confidence: 99%
“…The anterolateral thigh flap (ALT) is another workhorse flap for soft‐tissue reconstructions in the lower extremities. The ALT flap can provide a large skin paddle nourished by a long and large‐caliber pedicle . However, all free flaps have the common drawback of the difficulty of choosing the recipient vessels because of the poor local wound condition in the lower extremity .…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our results, Baek et al [14] and Smith et al [15] reported that most complications were venous thrombosis and congestion. Bianchi et al [16] and Kesting et al [17] reported several advantages of the anterolateral thigh flap for head and neck defects, including versatility, short harvesting time, and donor site morbidity. However, Kesting et al [17] reported that intra-operative arterial spasms occurred more often in the case of the ALT free flap than in the case of RFFF and that venous congestion was the most frequent complication in the case of the RFFF.…”
Section: Discussionmentioning
confidence: 99%
“…However, exposure of the donor site leading to considerable donor site morbidity has led surgeons to seek alternative solutions. The anterolateral thigh (ALT) flap, introduced by Song [6] and popularized by Wei [7,8], who considered it to be the ideal skin flap, is used by many teams for oropharyngeal reconstruction [2,9,10]. The thoracodorsal artery perforator (TDAP) flap, described in 1995 by Angrigiani et al [11], presents identical plastic qualities to those of the ALT, allowing it to be used in the oropharynx.…”
Section: Introductionmentioning
confidence: 98%
“…Resection of a cancer involving the lateral or superior wall of the oropharynx can lead to disorders of nose breathing, nasal regurgitation while feeding and hypernasal speech. Oropharyngeal reconstructions are designed to palliate these defects and numerous techniques have been proposed [1][2][3]. The radial forearm flap, described by Yang [4] and Song [5], due to its thin skin paddle, ease of dissection, the length of its pedicle and the calibre of its vessels, is the flap of choice for these reconstructions.…”
Section: Introductionmentioning
confidence: 99%